Optimal pricing strategy of hotel for long-term stay. (1st January 2012) - Ling, Liuyi; Guo, Xiaolong; He, Lina
Along with the economic development and tourism prosperity, long-term stay in hotel is very common in realistic practice in recent years. This paper does some research on how hotel pricing for long-term stay. By developing an operational optimisation model, this paper derives the optimal pricing strategy for long-term stay, and demonstrates that this strategy is beneficial to hotel as well as its customers. Moreover, this paper further analyses the effects on the optimal room rate and hotel revenue, of standard room rate, variable cost, hotel capacity, the number of individual customers, as well as the properties of long-term stay. Eventually, a numerical experiment is employed, and the results are consistent with reality.